2014
DOI: 10.1111/tesg.12093
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Sectoral Division of Labour within Central and Eastern European Countries: Evidence from Greenfield FDI

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
9
1
2
Order By: Relevance
“…Furthermore, the attraction forces of metropolises have drawn in foreign investors, enabling capital cities to strengthen their position within the national urban hierarchy. Dogaru et al (2014) have found that capital city regions in transitional Europe have received more greenfield FDIs and attracted a wider variety of investments, both in terms of sectors and functions. Largely, these findings would imply that "core" locations at the national level are better integrated through trade and capital flows than the rest of the urban areas in European transitional countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the attraction forces of metropolises have drawn in foreign investors, enabling capital cities to strengthen their position within the national urban hierarchy. Dogaru et al (2014) have found that capital city regions in transitional Europe have received more greenfield FDIs and attracted a wider variety of investments, both in terms of sectors and functions. Largely, these findings would imply that "core" locations at the national level are better integrated through trade and capital flows than the rest of the urban areas in European transitional countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, capital cities are the main location for headquarters of large firms and investors. Data on foreign investment inflows in transition economies mostly show that capital cities (or capital city/metropolitan regions) attract the bulk share of capital flows due to their superior business infrastructure and concentration of resources (Lintz et al, 2007;Dogaru et al, 2014). For these reasons a robustness check is performed by excluding manufacturing firms located in capital cities from the sample.…”
Section: Capital Cities' Economiesmentioning
confidence: 99%
“…Yet, despite wide-ranging locational advantages suited to diverse industry branches and the increasing flows of FDI, in the first half of the 2000s Central–Eastern European Countries [1] (CEEC) were attracting a mere fraction of cross-border investments conducted by multinational enterprises (MNEs) (UNCTAD, 2007; Dogaru et al , 2015; Ascani et al , 2017). Arguably, beyond the wider exogenous and geopolitical factors, this could be partially attributed to regional authorities' limited engagement in, and poor execution of promotion aimed at investment attraction.…”
Section: Introductionmentioning
confidence: 99%
“…The Czech Republic, Poland and Slovakia began emerging on the global map of FDI destinations only since the beginning of 1990s. As relative newcomers, from the outset they had to compete with established Western European destinations, with themselves and other locations in the neighbouring countries, Asia and Latin America (Helinska-Hughes and Hughes, 2003; Dogaru et al , 2015). Additionally, accession to the EU in May 2004 and the implementation of its acquis communautaire levelled the playing field and strengthened the competition between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation